Conceptualizing Autonomous Engagement in Participatory Sensing Design: A Deployment for Weight-Loss Self Monitoring Campaign - Anawar, Syarulnaziah; Pramudya Ananta, Gede; Zainal Abidin, Zaheera; Ayop, Zakiah; Yahya, Saadiah (2013)
User engagement is important in participatory sensing area to provide better understanding to measure user experience and define phenomena associated to participatory sensing application so that participants is motivated to use it. The objective of this paper is two-fold: First, to evaluate the impact of user engagement towards a participatory sensing campaign success. Second, to conceptualize newly autonomous engagement concept in participatory sensing design. For the first objective, a preliminary study is conducted that used data from a previous participatory weight-loss self-monitoring intervention program. The findings show that the metrics which are often used to measure user engagement is “not directly’ contribute to the success of participatory sensing campaign. To address the second objective, this paper introduces project w8L0ss which proposed an autonomous engagement concept, where participants have to be part of the decision-making process to achieve the intended goal. Autonomous Engagement; Participatory Sensing; Weight-Loss